Експериментальне дослідження обертального руху рідкого металу в індукційній канальній печі - Гориславець, Ю.М.; Глухенький, О.І. (Технічна електродинаміка, 2011)
On the physical model of induction channel furnace the structure of rotational motion of liquid metal in cylindrical channels is studied. Distribution of metal velocity on radius and length of furnace channel is received. The possibility of intensification of heat and mass transfer in induction furnace with rotational motion of metal by increasing the vortex motion of liquid metal in the longitudinal sections of cylindrical channels and emergence of transit flow in channel part of furnace is experimentally rotined.